Partial Discharge Measurement Using Transient Earth Voltage Sensors with Different Dimensions in Metal Shrouded Equipment - Dedi Tri Laksono; Deni Tri Laksono; Monika Faswia Fahmi; Umar Umar Khayam (International Journal of Science, Engineering, and Information Technology, 2023)
Partial discharge (PD) generally occurs in electrical equipment that is encased in metal. The metal box is a form of high voltage equipment such as Gas Insulated Switchgear (GIS), power switchgear. Indications of high-voltage electrical insulation failure can be detected by the appearance of partial discharge. One of the sensors to detect partial discharge is the Transient Earth Voltage (TEV) sensor. This study is to find the difference in detecting partial discharges in 3x3 cm handmade TEV sensors and 4x4 cm handmade TEV. The TEV sensor is positioned at the midpoint of the bushing area. A bushing is an area on high-voltage equipment where there is a small gap. The TEV sensor was placed at a distance of 15 cm, 30 cm, and 45 cm from the bushing. Some partial discharge measurements are in the form of partial discharge waveforms, partial discharge Inception Voltage, and phase patterns. Then the calculation is carried out on the frequency range of the TEV sensor. The source of partial discharge in the air insulation medium is a needle plate electrode. Based on the measurement results, both handmade TEV sensors can detect partial discharge in the ultrawide band frequency range. The result is that the 4x4 cm TEV sensor is better than the 3x3 cm TEV. This can be seen from the acquisition of PDIV, partial discharge waves, or capacitance values. Although the range of values is not large.